Penggunaan Konjungsi Dalam Buku Teks Bahasa Indonesia Kelas VII SMP - Aulia Sridarma Pertiwi, Fitri Nur; Hamsa, Akmal; Usman, Usman (Fakultas Teknik Universitas Negeri Makassar, 2024)
This study is a qualitative research that aims to describe the types and functions of conjunctions in Indonesian language textbooks of class VII junior high school. This research is a type of qualitative research. The data in this research is in the form of conjunctions in sentences contained in Indonesian textbooks of class VII junior high school. The source of the data is the Indonesian language textbook of junior high school/MTs class VII published by the Ministry of Education and Culture revised edition 2017. The data were collected using documentation, reading technique, note-taking technique and classification. The results of this study show that there are four types of conjunctions in Indonesian textbooks of grade VII in junior high school, namely coordinative conjunctions, subordinative conjunctions, correlative conjunctions, and inter-sentence conjunctions. The function of using conjunctions is to connect words with words, words with phrases, phrases with phrases, phrases with clauses, clauses with clauses, clauses with sentences, and sentences with sentences.